The Role of Islamic Education Teacher in Moral Education: A Case Study of (IIS) Malaysia - Muhammad Lawal, Adam A; Hussien, Suhailah (The International Institute for Science, Technology and Education, 2018)
The main purpose of this study is to investigate how the role of Islamic education teachers may influence in nurturing students’ morality. Teaching and nurturing students’ morality across curriculum is one of the important characteristics of the Integrated Curriculum for Secondary Schools in Malaysia. Its main drive is to enhance the potential of the individual students in a holistic, integrated and balanced manner that considers his spiritual, intellectual, emotional and physical growth. The researchers purposively selected two teaching staff from International Islamic School (IIS), Malaysia. The results of Semi-structured interviews revealed that teachers were satisfied about the process of teaching and nurturing students’ moral during the school hours. It was also found that negative influence of peers, some friends outside the school, parents at home had affected the students’ moral behaviour to some extent. The teachers felt that there is a need for support from the school administrator, parents, as well as media in order to reduce moral decay among students at school.